Late Cretaceous (Cenomanian-Maastrichtian) planktic foraminifera from Goban Spur (DSDP sites 549 and 550): Biostratigraphic inferences. (June 2018) - Luft de Souza, Fernanda; Krahl, Guilherme; Fauth, Gerson
Abstract: The planktic foraminifera from two sedimentary sequences of the Upper Cretaceous recovered by the Deep Sea Drilling Project (DSDP) Leg 80, Site 549 and Site 550 (Hole 550B) in the Goban Spur region were analysed in order to refine and integrate the zonal schemes for this area of the North Atlantic Ocean. In the studied intervals, 75 samples were analysed, and 88 species of planktic foraminifera were recognized, enabling the identification of the following biostratigraphic zones: Rotalipora cushmani (upper Cenomanian); Helvetoglobotruncana helvetica (lower Turonian); Dicarinella concavata (upper Turonian–Coniacian); Dicarinella asymetrica (upper Coniacian–Santonian); Racemiguembelina fructicosa and Abathomphalus mayaroensis (upper Maastrichtian). Two intervals in Hole 550B are likely correlative to composite biozones Pseudoguembelina palpebra/Gansserina gansseri (Campanian–Maastrichtian) and Racemiguembelina fructicosa/Abathomphalus mayaroensis (upper Maastrichtian). These zones indicate that the studied intervals were deposited from the late Cenomanian to the late Maastrichtian. The presence of high values (>6.6%) of Total Organic Carbon (TOC) in section 549-27-1 might be related to the Oceanic Anoxic Event 2 (OAE 2), globally recorded across the Cenomanian–Turonian boundary transition. The extinction of the Rotaliporidae family was observed in both sections and was associated with the onset of OAE2 in Site 549. Highlights: Recovery of planktonic foraminifera in the Cenomanian-Maastrichtian interval of Goban Spur, with eight biozones having been recognized. Variations in the planktonic foraminifera assemblages related to taphonomic processes. Faunal crisis during the Cenomanian/Turonian transition. Elevated values of TOC (6.6%) in the Cenomanian/Turonian transition associated to a Global Anoxic Event (OAE 2).